IMPLEMENTASI KEBIJAKAN PENETAPAN HARGA KOMODITAS KELAPA SAWIT DALAM RANGKA MEWUJUDKAN KESEJAHTERAAN PETANI: (Studi di Kabupaten Muaro Jambi) - Widiarti, Sri; Supriyono, Bambang; Hanafi, Imam (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2025)
Implementation of Palm Oil Commodity Pricing Policy in Order to Realize Farmers Welfare (Study in Muaro Jambi Regency). In The social background in Muaro Jambi Regency is closely related to the problem of land ownership distribution. Inequality in land ownership creates significant differences in farmers' ability to benefit from pricing policies. So that farmers with small plots of land often do not get maximum benefits compared to large farmers or companies. The results of the research method that the implementation of palm oil commodity pricing policies in Muaro Jambi Regency generally shows significant efforts from the government to maintain price stability and support farmer welfare. Factors that support the implementation of palm oil commodity pricing policies in Muaro Jambi Regency include good coordination between local and central governments, policies that encourage the use of technology, and the existence of training and incentive programs for farmers to increase productivity. While the inhibiting factors include slow bureaucracy, farmer resistance to pricing policies, and limited infrastructure that hinders the distribution of palm oil products to the market.